Participación ciudadana y control vecinal para generar valor público en la Municipalidad Distrital de Emilio San Martín, 2021 - Parimango Alvarez, Dennis Robert (2023)
This research has been developed with the purpose of determining if the exercise of the right of citizen participation, established in the Organic Law of Municipalities No. 27972, generates public value in the District Municipality of Emilio San Martín - Tamanco in the period 2021; The population surveyed were two hundred four (204) citizens or residents of the jurisdiction. The research is of a basic type, non-experimental, descriptive and mixed legal design. We conclude that the samples surveyed on citizen participation and neighborhood control were the following: in Table N° 01, 27.5% of the citizens surveyed were people over thirty years of age; in Table N° 02 the gender was constituted by male users at a rate of 59.8% and, female public at a rate of 40.2%. Table N° 03 shows that 52.9% of the population were users with secondary level studies; in Table N° 04, 39.7% of users reside in the jurisdiction for more than five years. In Table N° 05, the respondents stated that they were dissatisfied at a rate of 83.3% and, at a rate of 16.7%, they stated that they were satisfied. As can be seen in Table N° 06, 69.6% of respondents indicate that municipal management is inefficient and effective with services, while 30.4% indicate that municipal management is efficient and effective.